SMAR1 inhibits proliferation, EMT and Warburg effect of bladder cancer cells by suppressing the activity of the Wnt/β-catenin signaling pathway. Issue 2 (17th January 2023) - Bao, Pengfei; Li, Peng; Zhou, Xiaoqing; Zhang, Huijiang; You, Shengjie; Xu, Zhaoyu; Wu, Qi
ABSTRACT: This study aimed to investigate the effects of scaffold matrix attachment region binding protein 1 (SMAR1) on the development of bladder cancer (BCa). SMAR1 expression in paired tumor and corresponding adjacent normal tissues from 55 BCa patients was detected by quantitative reverse transcription-polymerase chain reaction. BCa cells were transfected to regulate SMAR1 expression. BCa cells were treated with XAV-939, LiCl and 2-deoxyglucose. The effect of SMAR1 on the viability, proliferation, migration, invasion and Warburg effect of BCa cells was researched by counting kit-8, colony formation assay, Transwell and aerobic glycolysis assays. Western blot was performed to detect protein expression. BCa cell growth in vivo was recorded in nude mice. Immunohistochemical staining was performed for clinical and xenografted tumor tissue specimens. SMAR1 expression was down-regulated in BCa patients, associating with worse prognoses. SMAR1 knockdown enhanced the viability, proliferation, migration, invasion, EMT and Warburg effect of BCa cells. The opposite effect was found in the SMAR1 overexpression BCa cells. XAV-939 treatment reversed the elevation of β-catenin, c-Myc and Cyclin D1 proteins expression and Warburg effect in Bca cells post-SMAR1 knockdown. LiCl treatment abrogated the inhibition of β-catenin, c-Myc and Cyclin D1 proteins expression and Warburg effect proteins due to SMAR1 overexpression in BCa cells. SMAR1 overexpression inhibited the growth of BCa cells in vivo. SMAR1 might suppress the Wnt/β-catenin signaling pathway activity to inhibit the progression of BCa. It might be an effective treatment target for BCa.